Applying Make a Match Technique to Improve the Seventh-Grade Of Students’ Vocabulary Mastery In SMP Dharma Wanita Medan - Meikardo Samuel Prayuda; Karisma Erikson Tarigan; Paulina Kezia Rajagukguk (Journal of English Language Learning, 2023)
The design of this research is Classroom Action Research (CAR). This research will observe and study the problems that arise in the implementation of the teaching and learning process. This study aims to prove that the make a match technique can improve the students' vocabulary mastery and to prove that the students' motivation in learning vocabulary is improved by using the make a match technique. This study used tests, questionnaires, observation sheets, and field notes as data collection instruments. The research results can be seen that applying the Make a Match Technique can successfully improve the students' vocabulary mastery. The students' mean score from the pre-test to post test. The students' mean score was 40 in the pre-test, the formative test was 62, and the post test was 80.